A potential method to confirm the previous existence of lawsonite in eclogite: the mass imbalance of Sr and LREEs in multistage epidote (Ganghe, Dabie UHP terrane). (6th February 2013) - Guo, S.; Ye, K.; Wu, T. F.; Chen, Y.; Yang, Y. H.; Zhang, L. M.; Liu, J. B.; Mao, Q.; Ma, Y. G.
Abstract Lawsonite is an important hydrous mineral that is stable at low‐temperature (LT) and high‐ to ultrahigh‐pressure (HP–UHP) conditions in subducted slabs. The occurrence/absence of lawsonite in eclogite is a significant constraint for the construction of the metamorphic, tectonic and fluid/melt evolution histories of an HP–UHP terrane. However, lawsonite is very rarely preserved in natural eclogites, and accurate judgment of its former existence is a significant challenge for petrologists. At present, whether lawsonite has ever existed in lawsonite‐absent eclogite is mainly judged by (i) pseudomorphs after lawsonite, and (ii) phase equilibria modelling. In this study, major element and trace‐element distributions in multistage minerals were examined in the Ganghe lawsonite‐absent UHP eclogite in the Dabie UHP terrane, eastern China. This work demonstrates that the whole‐rock Sr and light rare earth elements (LREEs) are mainly dominated by epidote; other minerals (garnet, omphacite, quartz, kyanite, barroisite, phengite and accessory minerals) play a very limited role in the Sr and LREEs budgets. Two stages of epidote, which have noticeably different Sr and LREEs contents, were recognized in the eclogite: (i) Epidote porphyroblasts (Ep‐P core), which are suspected to be the pseudomorphic mineral after lawsonite, contain significantly high Sr (7200–10 300 ppm) and LREEs (160–1300 ppm for La). (ii) An earlier stage epidote (Ep‐In core) occurs as inclusions in matrix omphacite, or in omphacite inclusions in the suspected pseudomorphic minerals after lawsonite (SPMAL); this early epidote has significantly lower Sr (990–1890 ppm, average 1495 ppm, n = 17) and LREEs contents (60–110 ppm for La, average 91 ppm, n = 17). All of the existing early‐stage minerals predating the SPMAL have very low contents of Sr and LREEs, and the total amounts of these elements in the early‐stage minerals do not balance those in the SPMAL. This indicates that a missing Ca‐, Al‐, Sr‐ and LREE‐rich mineral, which was previously in equilibrium with the early‐stage minerals, likely existed in the Ganghe eclogite. On the basis of the mineral geochemistry and phase equilibria modelling, we confirm that the missing mineral cannot be anything but lawsonite. This study indicates that examining the mass (im)balance of Sr and LREEs between multistage HP–UHP epidote can be used as a potential method to confirm the previous existence of lawsonite in lawsonite‐absent eclogite.